Effect of CrF3 on the corrosion behaviour of Hastelloy-N and 316L stainless steel alloys in FLiNaK molten salt. (February 2018) - Yin, Huiqin; Qiu, Jie; Liu, Huajian; Liu, Wenguan; Wang, Yang; Fei, Zejie; Zhao, Sufang; An, Xuehui; Cheng, Jinhui; Chen, Tao; Zhang, Peng; Yu, Guojun; et al.
Highlights: FLiNaK with the 0.4w.t.% CrF3 addition molten salt were prepared using our experimental device and procedures especially developed. Effect of corrosion product CrF3 on the corrosion behaviour of hastelloy-N and 316L stainless steel were studied for the first time. Synchrotron radiation X-ray diffraction (SR-XRD) with high sensitivity was adopted. Abstract: The effect of CrF3 on the corrosion behaviour of Hastelloy-N and 316L austenitic stainless steel alloys in FLiNaK at 700 °C was investigated using synchrotron radiation and other characterisation techniques. The results showed that CrF3 considerably accelerated the corrosion of both tested alloys by promoting the dissolution of Cr, Fe, and Mn from alloy matrices into molten salt. The 316L stainless steel alloys mainly exhibited intergranular corrosion, whereas the Hastelloy-N alloys tended to exhibit intergranular and pitting corrosion. After corrosion, the lattice parameter of both alloys decreased and Cr1.07 Fe18.93 was formed on the surface of the 316L stainless steel alloys.